Peran Circle Pertemanan Sebaya Seorang Muslim Terhadap Pembentukan Akhlakul Karimah - Fadilah, Nurul; Gunawan, Muhammad Randa (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
The purpose of this study was to determine the influence of peers on akhlakul karimah. This research uses a qualitative approach. Data collection methods are in-depth observation and interviews with informants. The selection of informants above is based on the principle of interest and closeness to the subject of this research. Data selection is in accordance with the research objectives that have been formulated; then the data in accordance with each formula is described in the research results and discussed with relevant concepts and theories and finally concluded. This conclusion is the answer to the main problem formulated in the introduction, namely the description of the influence of peer friendship on moral formation. The results of this study are the role of peers in shaping the morals of students majoring in biology education local A1 in 2022 based on friendships that bind togetherness, friendships that offer new information, social support from peers, the importance of sharing information from peers in interacting with others. friends, the intimacy of friendship with peers, the intimacy of friendship with peers, the importance of sharing information from peers in interacting with others. Friends, the intimacy of friendship with peers. Because friendship is a relationship between people based on reciprocity and mutual help. Trusting each other, loving each other and complementing each other in a way that creates a sense of security.